ANALISIS PENDAPATAN DAN KELAYAKAN BUDIDAYA SARANG BURUNG WALET DI KECAMATAN LUNYUK - Roos Nana Sucihati; U Usman; Rita Dwi Kantari (Jurnal Ekonomi & Bisnis, 2020)
The purpose of this study was to know the income and worthiness of swallow cultivation in Lunyuk District. Type of this study was a descriptive study with qualitative data types. Data were collected directly from primary sources through interviews and observation. The populations in this study were all swallow businessmen in Lunyuk District with number of population were 20 people and the entire population was used as census sample. The results of data analysis showed that the income obtained from swallow cultivation in Lunyuk District was higher than the costs incurred. Thus it can be concluded that the swallow cultivation business in Lunyuk District had advantages so it was feasible to continue.